LIVED RELIGIOUS MODERATION AND MUSLIM WOMEN’S AGENCY: An Indonesian Experience - Fauziah Nasution; Suparni Suparni; Farhani Azkia; Abdulroman Mahir (UIN Sumatera Utara, 2026)
This community-based qualitative study examines the role of Muslim women in strengthening religious moderation as a lived social practice within a Muslim minority community in North Sumatra, Indonesia. Data were collected through participant observations, focus group discussions, and in-depth interviews with Muslim women actively involved in majelis taklim and other community religious activities. The findings reveal that participants initially experienced limited understanding of religious moderation, social pressures associated with living in a multi-religious environment, and restricted access to gender-responsive religious education. Through community-based empowerment processes, women gradually reinterpreted religious moderation as a social and ethical responsibility rather than merely a formal religious obligation. As such they transformed into religious agency emerged as informal religious authority, acting as family educators, social mediators, and promoters of harmony. The originality of this study lies in conceptualizing religious moderation as a lived social practices negotiated through everyday experiences. This new perspective contributes to discussions on lived religion, women’s religious agency, and community-based empowerment while highlighting the importance of gender-sensitive religious education in strengthening social cohesion.Keywords: Religious Moderation, Muslim Women, Lived Religion, Community-Based Empowerment.